The Cornect family sings, plays music and talks about music - Thomas, Gerald (1973)
Les membres de la famille Cornect parlent de musique . Les petites filles de la famille chantent « Ton moulin, tu dors » [version de « Meunier, tu dors » ?] et « C’est l’aviron ». La famille joue et discute de la musique, puis Margaret Cornect chante « Goin’ away » et une autre chanson, qui est peut-être « Ode to Newfoundland » [?]. Ils parlent de la musique et de la valse et en jouent un exemple sur accordéon et guitare. -- Cornect family members talk about music. The little girls of the family sing "Ton moulin, tu dors" and "C'est l'aviron". The family plays and discusses music. Margaret Cornect sings "Goin' away" and another song, possibly "Ode to Newfoundland" [?]. They talk about music and the waltz and then play an example on accordion and guitar.